Nicolau syndrome due to diclofenac sodium (Voltaren®) injection: a case report - Kılıç, İnci (J Med Case Rep, 2014)
INTRODUCTION: Nicolau syndrome, also known as livedo-like dermatitis or embolia cutis medicamentosa, is a rare complication following the intramuscular or intra-articular injection of various drugs. CASE PRESENTATION: In our case report we report the case of a 45-year-old Turkish woman who developed Nicolau syndrome after an intramuscular injection in her right gluteal region of single-dose diclofenac sodium to treat a headache. A culture taken from the ulcer showed growth of methicillin-sensitive Staphylococcus aureus on the 10(th) day. The secondary staphylococcal infection was treated effectively with intravascular ampicillin-sulbactam (4×1.5g/day). She was treated with surgical debridement, sterile dressings and analgesics. The ulcer healed completely within 12 weeks with scarring. CONCLUSIONS: Although Nicolau syndrome develops very rarely, it is an important cause for morbidity. It is an iatrogenic condition, treated mostly by health care workers. Thus, although it appears to be a very simple procedure for a health care worker, care must be taken during intramuscular injections. Although diclofenac sodium is a widely used non-steroidal anti-inflammatory drug, Nicolau syndrome following intramuscular diclofenac sodium injection has rarely been reported in the published literature. The application of a cold compress was considered to be an aggravating factor in our patient. This case highlights the need for awareness about this condition and the need to exercise utmost care during the administration of any parenteral injections by health workers.